Being a muslim a fact or a challenge and its implication for islamic education - Kazmi, Yedullah (2009)
This article investigates the issue of self-identity and its implications for a Muslim. The article further explores the consequences for Muslims for making their identity as Muslims an issue, and then makes tentative suggestions regarding education that would follow from such a decision. This exploration is guided by the logic of the distinction between ‘who is a Muslim’ and ‘what is it to be a Muslim.’ The issue of identify is framed not in the context of such cultural phenomenon as identity crisis but couched in terms of existential challenge of being either a Muslim by accident of birth or consciously and purposely designing oneself as a Muslim by making it as one’s life-project. The choice being between being Muslim as a social fact with little or no input of one’s own or taking the ethical responsibility to fashion oneself in the light of the Qur’┐n.